Building Cisco Remote Access Networks - Edwards, Mark (Syngress Publishing, Inc., 2011)
An increasing number of companies are designing and implementing Remote Access Networks, which allow users who are not physically connected to a Wide Area Network (WAN) or Local Area Network (LAN) to access the network's servers, applications and databases or to participate in video conferencing and conference calls. The ability for a remote user to function as if they were in the next office dramatically improves overall efficiency while reducing total cost of ownership. Cisco Systems, the world's largest internetworking vendor, is the pioneer of the enabling technologies for Remote Access Networks. This book will identify and explain all of the Cisco products necessary for designing and building a remote access network and integrating it with legacy systems.